EMPOWERING SPEAKING ABILITY FOR EFL STUDENTS USING PSYCHOLOGY GAME TECHNIQUE TO THE SECOND GRADE STUDENTS’ AT SMAN 2 BULUKUMBA - Saiful, Saiful; Bakri, Rina Asrini; Ilmiah, Ilmiah (JOURNAL OF ADVANCED ENGLISH STUDIES, 2018)
The aim and cord point of this research is to apply psychology game in order to improve EFL students’ speaking skill. The researcher employed quasi experimental method for the study. The data resources was 40 students at the third grade students of SMAN 2 Bulukumba, they were choosen randomly. The instrument for the research was the speaking test. In analyzing data the researcher collected the speaking test in line with the instrument test and analyzed in scoring, fluency, accuracy and comprehensibility of the students speaking. From all the data, the result of posttest showed higher than pretest result using psychology game in learning speaking of SMAN 2 Bulukumba. It was proved by the t-test (4.405) greater than t-table (2.024). it means that the students speaking achievement can be built. Besides the study explained that comparing the students pretest and posttest (31.35<59.50), the students in class II IPA 2 and II IPA 1 (25.10< 36.30) have a significant difference which the students who treated was better than the student in a control class. The result of the research showed that The speaking ability of the second grade students at SMAN 2 Bulukumba has been improved after having and applying psychology game.